(untitled) (International Journal of Engineering and Computer Science, 2020)
The aim of the study was to analyze the dynamic response along an aluminum cantilever beam. The data measured were displacement (mm), velocity (mm / s), and acceleration (m/s2) with 3 variations of the measurement position on the beam. The 6061 series aluminum beam used have length: 80 cm, height: 32 cm, and width: 32 cm. Data were collected experimentally using a vibration meter to measure beam vibrations at the various positions from the cantilever beam at a distance from support: 10 cm, 35 cm, and 60 cm. The results of the analysis showed that the values ​​of the displacement, velocity and acceleration of the object vibrations change when the measuring point was far from the cantilever support. The maximum displacement value is at 60 cm from the support: 0.02 mm, and the lowest is at 10 cm: 0.12 mm. The velocity value also increases, maximum at 60 cm from the support: 38.58 mm/s and the minimum value at 10 cm: 12.30 mm/s. While the acceleration value, the maximum at 60 cm from the support: 91150 mm/s2 and the minimum at 10 cm: 66900 mm/s2.